Analisa Efektifitas Keberlangsungan Kegiatan Bisnis UMKM Ayam Geprek Dapur Cece - Asri, Dhita Hafizha; Lim, Jesson; Ricky, Ricky; Andiko, Riki; Esfandiany, Shelby; Winston, Winston (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
MSME is one of the industrial sectors that contributes the most to the income of the Indonesian citizens. This is in line with the very rapid development of technology and information systems, which can provide opportunities and opportunities for MSME actors to develop and expand their business goals, both by increasing marketing and implementing promotional strategies to be able to increase market reach. One of the MSMEs that utilizes information technology and systems is the Ayam Geprek Dapur Cece MSME located in Batam City. This study aims to analyze the effectiveness of the business continuity of UMKM Ayam Geprek Dapur Cece, related to the marketing strategy that they carry out through sosial media, as well as related to key motivational techniques which are equally important for them to implement. The research method applied is in the form of a qualitative method, by carrying out observation activities, as well as literature review or literature review. The results showed that the implementation of marketing strategies through sosial media with the application of key motivational techniques had a significant and positive effect on the effectiveness of the business counter of UMKM Ayam Geprek Dapur Cece.